2020
DOI: 10.1021/acs.joc.0c01685
|View full text |Cite
|
Sign up to set email alerts
|

In Search of 1,4-Diazabutatrienes, the Elusive Isocyanide Homodimers: The Superchameleonic F–NC

Abstract: Figure 1. (a) Resonant forms of isocyanides 1 and (b) homodimerization of isocyanides 1 to afford 1,4-diazabutatrienes 2. Note pubs.acs.org/joc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recently, we published a theoretical study dealing with the homodimerization of isocyanides 47 towards 1,4-diazabutatrienes 49 (Scheme 11). 81–83 As in the dimerization of carbenes we observed that the habitually chameleonic 84 isocyanides follow a non-least-motion pathway along the reaction coordinate via the transition state 48 . Although in most of the cases both monomers behave equally along the non-least-motion reaction coordinate, in a few cases the independent monomers differ each other not only at the transition state structure but also at the early stages of the reaction, as is the case of the dimerization of F–NC, MeO–NC and SMe–NC.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, we published a theoretical study dealing with the homodimerization of isocyanides 47 towards 1,4-diazabutatrienes 49 (Scheme 11). 81–83 As in the dimerization of carbenes we observed that the habitually chameleonic 84 isocyanides follow a non-least-motion pathway along the reaction coordinate via the transition state 48 . Although in most of the cases both monomers behave equally along the non-least-motion reaction coordinate, in a few cases the independent monomers differ each other not only at the transition state structure but also at the early stages of the reaction, as is the case of the dimerization of F–NC, MeO–NC and SMe–NC.…”
Section: Introductionmentioning
confidence: 81%